PENGARUH EKSTRAK DAGING LIDAH BUAYA (Aloe Vera) TERHADAP PENYEMBUHAN ULSERASI MUKOSA MULUT PADA MALE WISTAR RATS - Laila Fitrotuz Zahroh; Rahmawati Sri Praptiningsih; Moh. Baehaqi (Odonto : Dental Journal, 2014)
Background: Oral mucosa ulceration which often occurs usually in the form of white-yellowish spot with concave surface, reddish edge and pain. Based on previous research, Aloe vera process anti-inflammation substance that could help quickening ulceration healing process. This research aims to know the effect of Aloe vera flesh extract on Male wistar rats oral mucosa ulceration in-vivo. Method: this research was quasi experimental research with the post-test only control group design using Male wistar rats as the testing animal. In the research, there were three treatment groups: The first groups which was given aquadest treatment, second groups with Aloe vera flesh extract, and third groups which was given chlorhexidine gluconate 0,2% treatment. The data collecting was based on histopathology observation concerning the increase of fibroblast quantity. Result: The research result based on comparison test among the three groups with One Way Anova showed that on Day 3th, the average quantity of fibroblast didn't have significant difference between the treatment group and control group positive that was p>0,05, meanwhile on Day 7th every group showed significant difference p<0,05. Conclusion: It concluded that Aloe vera flesh extract has influence on the healing of Male wistar rats oral mucosa ulceration as shown by fibroblast increasing quantity.